Simple bare gold nanoparticles for rapid colorimetric detection of Cr3+ ions in aqueous medium with real sample applications - Shellaiah, Muthaiah; Simon, Turibius; Sun, Kien Wen; Ko, Fu-Hsiang (My University, 2016)
Facile bare gold nanoparticles (AuNPs) were synthesized via borohydride reduction method and evidenced the colorimetric sensor selectivity to Cr3+ ions among Na+, Ni2+, Fe3+, Cd2+, Cr3+, Cu2+, Ca2+, Mg2+, Ga3+, Fe2+, Ba2+, Al3+ Ag+, Co2+, Zn2+, Pb2+, Mn2+ and Hg2+ ions. The color of bare AuNPs changed rapidly from red to blue via Cr3+ induced aggregation. These Cr3+-induced aggregation of bare AuNPs were monitored by naked eye and using UV-vis spectroscopy. The SPR absorbance (654 nm) of the reaction between bare AuNPs and Cr3+ showed a good linearity with a low detection limit of 13.42 nM. The optimal detection of Cr3+ was achieved between pH ranges from 5 to 11 and its reversibility was well established with EDTA. In addition, the bare AuNPs which were successfully applied for the detection of Cr3+ in tap and lake water displays low interference. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Bare gold nanoparticles; Cr3+; Colorimetric sensor; Real sample analysis